2007
DOI: 10.2164/jandrol.107.003350
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship Between Sperm Morphology and Chromatin Integrity in the Koala (Phascolarctos cinereus) as Assessed by the Sperm Chromatin Dispersion Test (SCDt)

Abstract: Koala (Phascolarctos cinereus) sperm nuclei show a tendency to swell after cryopreservation, but it is uncertain whether this phenomenon is associated with DNA fragmentation. In this study, we validated a modified version of the sperm chromatin dispersion test (SCDt) for use with koala spermatozoa, which is the first use of the test for a marsupial. Cryopreserved spermatozoa (multiple straws) from a single koala were used to explore the relationship between sperm morphology, viability, chromatin dispersion, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
23
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 38 publications
(27 citation statements)
references
References 28 publications
3
23
0
Order By: Relevance
“…This range of SCDt morphotypes has now been documented in the current study and supersedes the descriptors previously provided in Johnston et al (2007).…”
Section: Discussionsupporting
confidence: 85%
“…This range of SCDt morphotypes has now been documented in the current study and supersedes the descriptors previously provided in Johnston et al (2007).…”
Section: Discussionsupporting
confidence: 85%
“…SDF was determined using a Halomax kit (Halotech SL, Madrid, Spain) previously validated and described for koala spermatozoa first by Johnston et al (2007) and then refined by Zee et al (2009b). ISNT of DNA breaks was determined on cryopreserved semen samples (nZ2).…”
Section: Assessment Of Semen Qualitymentioning
confidence: 99%
“…We have not investigated this aspect in detail here, but similar results were found in koalas where protein depletion was produced in the absence of dithiothreitol (DTT): a specific treatment to weaken disulphide bonds in protamines. Johnston et al (2007) suggested a model of sperm chromatin organization in koalas where the tight organization of the sperm haploid genome required the distribution of non-orthodox DNA motifs, such as abasic sites or single-stranded DNA stretches, resident throughout the chromatin that allows specific sperm DNA packaging, but also show proclivity to be broken by processes such as freeze thawing and chromatin swelling (Johnston et al 2006). Such sites may allow extreme compaction in the absence of S-S bonding-mediated protamination, but also render the chromatin much more vulnerable to artificial stressors at these sites.…”
Section: T0mentioning
confidence: 99%